IMAGE PROCESSING APPARATUS AND METHOD, AND PROGRAM - MORIFUJI TAKAFUMI; USHIKI SUGURU; OGATA MASAMI (2012)
PROBLEM TO BE SOLVED: To accurately detect the parallax of a stereoscopic image composed of a right image and a left image.SOLUTION: A parallax detection unit generates, from a right image and a left image, a parallax map indicating the parallax of each pixel in the images, and generates a reliability map indicating likelihood of the parallax. A depth information estimation unit, from the right image or the left image, generates a depth information map indicating the depth of a subject on the image. A depth parallax conversion unit converts the depth information map into a pseudo parallax map using a conversion expression for converting depth information into parallax information. A parallax synthesis unit synthesizes the parallax map and the pseudo parallax map using the reliability map to generate a corrected parallax map. The present invention is applicable to an image processing apparatus.